Essential/precursor chemicals and drug consumption: impacts of US sodium permanganate and Mexico pseudoephedrine controls on the numbers of US cocaine and methamphetamine users. (16th August 2016) - Cunningham, James K.; Liu, Lon‐Mu; Callaghan, Russell C.
Abstract: Background and Aims: In December 2006 the United States regulated sodium permanganate, a cocaine essential chemical. In March 2007 Mexico, the United States' primary source for methamphetamine, closed a chemical company accused of illicitly importing 60+ tons of pseudoephedrine, a methamphetamine precursor chemical. US cocaine availability and methamphetamine availability, respectively, decreased in association. This study tested whether the controls had impacts upon the numbers of US cocaine users and methamphetamine users. Design: Auto‐regressive integrated moving average (ARIMA) intervention time–series analysis. Comparison series—heroin and marijuana users—were used. Setting: United States, 2002–14. Participants: The National Survey on Drug Use and Health ( n = 723 283), a complex sample survey of the US civilian, non‐institutionalized population. Measurements: Estimates of the numbers of (1) past‐year users and (2) past‐month users were constructed for each calendar quarter from 2002 to 2014, providing each series with 52 time‐periods. Findings: Downward shifts in cocaine users started at the time of the cocaine regulation. Past‐year and past‐month cocaine users series levels decreased by approximately 1 946 271 (−32%) ( P < 0.05) and 694 770 (−29%) ( P < 0.01), respectively—no apparent recovery occurred through 2014. Downward shifts in methamphetamine users started at the time of the chemical company closure. Past‐year and past‐month methamphetamine series levels decreased by 494 440 (−35%) [ P < 0.01; 95% confidence interval (CI) = −771 897, −216 982] and 277 380 (−45%) ( P < 0.05; CI = −554 073, −686), respectively—partial recovery possibly occurred in 2013. The comparison series changed little at the intervention times. Conclusions: Essential/precursor chemical controls in the United States (2006) and Mexico (2007) were associated with large, extended (7+ years) reductions in cocaine users and methamphetamine users in the United States.